Analysis Of Code Switching On Sunny Dahye Instagram Account - Isnaini, Janatun; Anindita, Widyashanti K (LPPM Universitas Pekalongan, 2022)
This research is a descriptive qualitative research. The data in this study are the captions and comments of Sunny Dahye Instagram account. Technique of collecting data is documentation which is online Instagram. Technique of analyzing data is reducing data, displaying data and conclusion. To validate the data, the researchers used the triangulation data based on source, method, researcher and theory.The research findings show that the types of code switching found on Sunny Dahye Instagram account are inter sentential switching with 72 utterances, intra sentential switching with 24 utterances, and tag switching / emblemtic switching with 4 utterances, The dominant types of code switching is inter sentential switching by the reasons of talking about particular topic with 18 utterances, interjection with 5 utterances, expressing group identity with 10 utterances, being emphatic about something with 8 utterances, repetition used for clarification with 12 utterances, to soften and strengthen request or command with 42 utterances, real lexical need with 5 utterances. Based on the finding, it can be drawn that Sunny Dahye Instagram account do not use quoting somebody else and to exclude other people when a comment is intended for only limited audience in her captions and comments. Keywords: Code Switching, Types and Reasons of Code Switching, Sunny Dahye, Caption, Comment.